2021
DOI: 10.1038/s41420-021-00717-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CK2 in cancer: a valuable strategy or a waste of time?

Abstract: CK2 is a protein kinase involved in several human diseases (ranging from neurological and cardiovascular diseases to autoimmune disorders, diabetes, and infections, including COVID-19), but its best-known implications are in cancer, where it is considered a pharmacological target. Several CK2 inhibitors are available and clinical trials are underway in different cancer types. Recently, the suitability of CK2 as a broad anticancer target has been questioned by the finding that a newly developed compound, named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Reducing the expression of CK2 subunits with siRNA resulted in a decreased proliferation, survival, migration, and invasiveness in malignant glioma cells and a variety of other cancer cells. Knockout of CK2 with the use of CRISPR technology further confirmed reduced cell proliferation, motility, and invasiveness as a result of CK2 targeting [96].…”
Section: Effects Of Silencing Ck2 On Glioma Developmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Reducing the expression of CK2 subunits with siRNA resulted in a decreased proliferation, survival, migration, and invasiveness in malignant glioma cells and a variety of other cancer cells. Knockout of CK2 with the use of CRISPR technology further confirmed reduced cell proliferation, motility, and invasiveness as a result of CK2 targeting [96].…”
Section: Effects Of Silencing Ck2 On Glioma Developmentmentioning
confidence: 84%
“…Nevertheless, it seems that any reliable conclusions should be withdrawn at this point, considering that the investigation is still ongoing. In addition, recent reports seem to have indicated that other inhibitors under development that are more specific than CX-4945 showed anticancer effect [96].…”
Section: Cx-4945mentioning
confidence: 99%
“…Use of ATP-competitive kinase inhibitors as chemical probes for target validation in cells can often be confounded by poor selectivity especially at high micromolar doses. For example, it has been proposed that the antiproliferative effects of silmitasertib may result from inhibition of kinases other than CSNK2 (25, 36) due to its modest selectivity. Application of multiple chemogenomic methods can be used to strengthen the association of a cell phenotype with a specific kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wells et al [27] suggested SGC-CK2-1 (IC50 = 36 nM) as an efficient CK2 inhibitor [27]. This molecule is considered as non-toxic and, thus, has been proposed to be suitable not only for the treatment of cancers, but also for other pathological conditions, such as neurodegenerative diseases [27,40].…”
Section: Discussionmentioning
confidence: 99%